Peripheral Serum Thyroxine, Triiodothyronine and Reverse Triiodothyronine Kinetics in the Low Thyroxine State of Acute Nonthyroidal Illnesses: A NONCOMPARTMENTAL ANALYSIS - Kaptein, Elaine M. (1982)
The low thyroxine (T(4)) state of acute critical nonthyroidal illnesses is characterized by marked decreases in serum total T(4) and triiodothyronine (T(3)) with elevated reverse T(3) (rT(3)) values. To better define the mechanisms responsible for these alterations, serum kinetic disappearance studies of labeled T(4), T(3), or rT(3) were determined in 16 patients with the low T(4) state and compared with 27 euthyroid controls and a single subject with near absence of thyroxine-binding globulin. Marked increases in the serum free fractions of T(4) (0.070±0.007%, normal [nl] 0.0315±0.0014, P < 0.001), T(3) (0.696±0.065%, nl 0.310±0.034, P < 0.001), and rT(3) (0.404±0.051%, nl 0.133±0.007, P < 0.001) by equilibrium dialysis were observed indicating impaired serum binding. Noncompartmental analysis of the kinetic data revealed an increased metabolic clearance rate (MCR) of T(4) (1.69±0.22 liter/d per m(2), nl 0.73±0.05, P < 0.001) and fractional catabolic rate (FCR) (32.8±2.6%, nl 12.0±0.8, P < 0.001), analogous to the euthyroid subject with low thyroxine-binding globulin. However, the reduced rate of T(4) exit from the serum (Kii) (15.2±4.6 d(−1), nl 28.4±3.9, P < 0.001) indicated an impairment of extravascular T(4) binding that exceeded the serum binding defect. This defect did not apparently reduce the availability of T(4) to sites of disposal as reflected by the increased fractional disposal rate of T(4) (0.101±0.018 d(−1), nl 0.021±0.003, P < 0.001). The decreased serum T(3) binding was associated with the expected increases in MCR (18.80±2.22 liter/d per m(2), nl 13.74±1.30, P < 0.05) and total volume of distribution (26.55±4.80 liter/m(2), nl 13.10±2.54, P < 0.01). However, the unaltered Kii suggested an extravascular binding impairment comparable to that found in serum. The decreased T(3) production rate (6.34±0.53 μg/d per m(2), nl 23.47±2.12, P < 0.005) appeared to result from reduced peripheral T(4) to T(3) conversion because of decreased 5′-deiodination rather than from a decreased T(4) availability. This view was supported by the normality of the rT(3) production rate. The normal Kii values for rT(3) indicated a comparable defect in serum and extravascular rT(3) binding. The reduced MCR (25.05±6.03 liter/d per m(2), nl 59.96±8.56, P < 0.005) and FCR (191.0±41.19%, nl 628.0±199.0, P < 0.02) for rT(3) are compatible with an impairment of the rT(3) deiodination rate. These alterations in thyroid hormones indices and kinetic parameters for T(4), T(3), and rT(3) in the low T(4) state of acute nonthyroidal illnesses can be accounted for by: (a) decreased binding of T(4), T(3), and rT(3) to vascular and extravascular sites with a proportionately greater impairment of extravascular T(4) binding, and (b) impaired 5′-deiodination activity affecting both T(4) and rT(3) metabolism.